Reply to comment by Rashid et al. on "Asynchronous variation in the East Asian winter monsoon during the Holocene" - Jin, Liya; Zhang, Xiaojian; Leduc, Guillaume (Journal of Geophysical Research: Atmospheres, 2016)
Rashid et al. (2016) questioned the use of the Mg-/Ca-based sea surface temperature (SST) data from the subpolar North Atlantic Ocean as well as the alkenone-based SST data from the western tropical Indian Ocean we used to reflect the winter SSTs or regional changes in the Holocene SSTs. We first would like to reemphasize that the main message we wanted to convey in our article is that the East Asian winter monsoon (EAWM) strength decreased and then increased again during the Holocene but with a substantial lag in southern China as compared to northern China. We, of course, wanted to back up our model results with published SST data that may have detected such an asynchronous variation in the EAWM. For convenience, we used a series of proxy records extracted from the extended Global database for alkenone-derived HOlocene Sea-surface Temperature (GHOST) database that were initially intended to provide a template of Holocene SST trends for model/data comparison purpose (). Rashid et al. (2016) questioned our model/data comparison exercise, arguing that the data we present in Zhang et al. (2015a) cannot be used to track leads and lags in winter SSTs in the North Atlantic and northern Indian Ocean. Below we address point by point the issues raised by Rashid et al. (2016) and thank the authors for giving us the opportunity to sharpen our model/data comparison analysis.